Strategy development and renewal due to changes in value chain - Niemi-Korpi, Hanna (My University, 2023)
Business strategies must develop at a fast pace to stay relevant. In a changing business envi-ronment, strategy development is essential to stay alive. Value chain changes affect the strategy, and when changes are made in the value chains, they also affect the strategy. Part-nerships are becoming increasingly essential for companies, and the competition to have good partnerships is hard. Knowing how partnerships should be nurtured and led to devel-opment is essential. This study examines how value chain changes affect the strategy and how service partner-ships should be led and developed from both sides. Data is collected as secondary data from the company, annual reports, sustainability reports, and other written material provided by the company. Data is also collected through interviews that show how service partnerships should be led and developed. The findings of this study show that when changes are made in the value chain, the strategy must develop as well. The findings also show how the company strategy has developed over the years and how the focus has shifted. In order to do innovative business with motivated personnel, the company strategy focused much on customer service and customer satisfac-tion. The deepened cooperation with partners also required insight from the partners and the company on developing the partnerships. The findings show that depending on the an-swerer, cooperation is seen differently. However, the main goal is that both partners benefit from the cooperation and understand why the cooperation is essential. If the partners see the current state of the cooperation or the target state differently, the development of the partnership may be complex.
Keywords: strategies; value chains; partnership; cooperation (general); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development